Combining Intensive Counseling by Frontline Workers with a Nationwide Mass Media Campaign Has Large Differential Impacts on Complementary Feeding Practices but Not on Child Growth: Results of a Cluster-Randomized Program Evaluation in Bangladesh. Issue 10 (31st August 2016) - Menon, Purnima; Nguyen, Phuong Hong; Saha, Kuntal Kumar; Khaled, Adiba; Sanghvi, Tina; Baker, Jean; Afsana, Kaosar; Haque, Raisul; Frongillo, Edward A; Ruel, Marie T; Rawat, Rahul
Abstract: Background : Complementary feeding (CF) contributes to child growth and development, but few CF programs are delivered at scale. Alive & Thrive addressed this in Bangladesh through intensified interpersonal counseling (IPC), mass media (MM), and community mobilization (CM). Objective: The objective was to evaluate the impact of providing IPC + MM + CM (intensive) compared with standard nutrition counseling + less intensive MM + CM (nonintensive) on CF practices and anthropometric measurements. Methods: We used a cluster-randomized, nonblinded evaluation with cross-sectional surveys [ n = ∼600 and 1090 children 6–23.9 mo and 24–47.9 mo/group, respectively, at baseline (2010) and n = ∼500 and 1100 children of the same age, respectively, at endline (2014)]. We derived difference-in-difference impact estimates (DDEs), adjusting for geographic clustering, infant age, sex, differences in baseline characteristics, and differential change in characteristics over time. Results: Groups were similar at baseline. CF improvements were significantly greater in the intensive than in the nonintensive group [DDEs: 16.3, 14.7, 22.0, and 24.6 percentage points (pp) for minimum dietary diversity, minimum meal frequency, minimum acceptable diet, and consumption of iron-rich foods, respectively]. In the intensive group, CF practices were high: 50.4% for minimum acceptable diet, 63.8% for minimum diet diversity, 75.1% for minimum meal frequency, and 78.5% for consumption of iron-rich foods. Timely introduction of foods improved. Significant, nondifferential stunting declines occurred in intensive (6.2 pp) and nonintensive (5.2 pp) groups in children 24–47.9 mo. Conclusions: The intensive program substantially improved CF practices compared with the nonintensive program. Large-scale program delivery was feasible and, with the use of multiple platforms, reached 1.7 million households. Nondifferential impacts on stunting were likely due to rapid positive secular trends in Bangladesh. Accelerating linear growth further could require accompanying interventions. This study establishes proof of concept for large-scale behavior change interventions to improve child feeding. This trial was registered at clinicaltrials.gov as NCT01678716.